2017
DOI: 10.3389/fimmu.2017.00379
|View full text |Cite
|
Sign up to set email alerts
|

Human Scavenger Receptor A1-Mediated Inflammatory Response to Silica Particle Exposure Is Size Specific

Abstract: The application of nanotechnology in the health care setting has many potential benefits; however, our understanding of the interactions between nanoparticles and our immune system remains incomplete. Although many of the biological effects of nanoparticles are negatively correlated with particle size, some are clearly size specific and the mechanisms underlying these size-specific biological effects remain unknown. Here, we examined the pro-inflammatory effects of silica particles in THP-1 cells with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Because particle size influences the competence of immune responses induced by vaccination, it must be considered when vaccine formulations are intended for intranasal immunization . It has been frequently reported that particle size influences immune responses . With regard to vaccine Ags, it has been noted that only particles in the nanometre range, that is of the size of viruses, can reach lymph nodes and directly interact with B cells, inducing potent immune responses .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because particle size influences the competence of immune responses induced by vaccination, it must be considered when vaccine formulations are intended for intranasal immunization . It has been frequently reported that particle size influences immune responses . With regard to vaccine Ags, it has been noted that only particles in the nanometre range, that is of the size of viruses, can reach lymph nodes and directly interact with B cells, inducing potent immune responses .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to vaccine Ags, it has been noted that only particles in the nanometre range, that is of the size of viruses, can reach lymph nodes and directly interact with B cells, inducing potent immune responses . Comparisons of silica nanoparticle vaccines that contained particles of different diameters demonstrated that particles of the most effective formulations were 30‐50 nm in diameter . Synthetic haemozoin preparations that comprised 50‐200‐nm particles exhibited a stronger adjuvant effect compared with preparations with larger (2‐20 μm) or smaller (<50 nm) particles .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The key components of natural and synthetic polymers had been clearly identified and all that was required were processes to allow the manufacture of nanoparticles. Since functionality of nanoparticles is often associated with smaller sizes a practical definition of 1-100 nm has been adopted widely but clearly the scientific definition is derived from fundamental length dimension of particles in sizes smaller than 1,000 nm (Commissioner O.o.t., 2014;Nishijima N. et al, 2017).…”
Section: Introductionmentioning
confidence: 99%